The development and validation of a skinfold-thickness prediction equation in high level futsal athletes - Matias, C. N.; Santos, D. A.; Giro, R.; Cavaca, M. L.; Faleiro, J.; Oliveira, M.; Duque, P.; Vicente, F.; Pereira, P.; Teixeira, V. H.; Teixeira, F. J. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Specific and practical approaches to estimate fat mass (FM) in athletes are warranted, especially regarding team sports athletes, i.e. futsal players. Assessing skinfold (SKF) thickness and body girth is a simple field technique to evaluate FM, especially when performed by an ISAK (The International Society for the Advancement of Kinanthropometry) certified practitioner. The aim of this study was to develop and cross-validate an anthropometric equation for FM estimation in a sample of male futsal players using ISAK SKF and body girth as variables vs. the dual X-ray absorptiometry (DXA) fat mass (%) output.